Perlindungan Hukum Terhadap Buruh/TenagaKerja Indonesia Yang Bekerja Di Luar Negeri(Suatu Tinjuan Dari Hukum Perdata) - Widyatmoko, Widyatmoko, Nuswardani, S.H., S.U, Shalman Al Farizi, S.H., M.Kn (2016)
Each the candidates of migrants workers have the right to be protected in accordance with the legislation in force. Government, private ( recruitment agency), and overseas business partners are required to provide protection to migrant workers, the coordination of the parties is necessary in order to achieve the protection of the safety of workers. The rise of cases involving migrant workers recently showed that the protection of migrant workers has not been carried out to the maximum by the parties. Based on the above there are some formulations of the problem: (1) What is the process sustainable of Kridatama recruitment agency agreements with labor migrants working abroad? (2) How can the rights and obligations of the parties, as well as the regulations in effect that relates to the migrant workers? (3) How is the responsibility of these agencies or migrant workers when in default? By comparing the legislation in force, the employment of agreements and the implementation of migrant workers, it known whether the placement and protection of migrant workers in accordance with applicable regulations or not. From the results of the placement process conducted by the recruitment agency of Kridatama Bina Lestari there are three (3) the agreements, there are the agreement recruitment, placement agreements and employment agreements containing rights and obligations of each party. However, in the agreement less mention in detail about the rights and obligations of the parties, it is very influential on the protection of migrant workers. To guarantee the rights and obligations of the parties and the protection of migrant workers, furthermore the agreements mentioned above need to be improved so that the rights and obligations of the parties can be arranged in detail, so the protection of migrant workers to be more secure.